Electromyographic Activity of the Transversus Abdominis and Erector Spinae Muscles During the Y-Balance Test - Utku Umut, Gülsena; Korkmaz Dayıcan, Damla; Özyürek, Burçin; Hoşbay, Zeynep (Sportverletzung · Sportschaden, 2025)
This study aimed to investigate the electromyographic activity of the transversus abdominis (TrA) and erector spinae (ES) muscles in three different directions during the Y-Balance Test (YBT), and to assess the co-activation between these muscles. A total of twenty-four participants (mean age = 22.71 ± 1.48 years) were evaluated. Electromyographic data from the TrA and ES were recorded using surface electromyography (sEMG) during the YBT. The results revealed that the mean and maximum activity of the TrA in the anterior direction, with the dominant extremity on the ground, was significantly higher (p = 0.014). Additionally, the mean activity of the TrA (p = 0.030) and both the mean (p < 0.001) and maximum (p = 0.047) activity of the ES in the posteromedial direction, with the dominant extremity on the ground, were significantly elevated. The onset times of the TrA and ES contractions were correlated in posteromedial and posterolateral directions, irrespective of extremity dominance (p<0.05). Furthermore, correlations were observed between the mean TrA activity and the onset of ES (r = 0.447, p = 0.029), as well as between the mean ES value and the onset of TrA (r = 0.430, p = 0.036), in the posteromedial direction. This study concluded that TrA activation was most pronounced in the anterior direction with the dominant extremity on the ground, whereas the highest co-activation of the TrA and ES occurred in the posteromedial direction when the non-dominant extremity was on the ground.
Keywords: dynamic balance; electromyography; transversus abdominis; erector spinae